Oxygen isotopic composition of limpet shells from the Beagle Channel: implications for seasonal studies in shell middens of Tierra del Fuego - Colonese, André Carlo (2012)
Shell middens distributed along the coastal areas of the Beagle Channel (Tierra del Fuego) testify the primary role of marine resources in the successful social dynamic of hunter-gatherer-fisher societies (HGF) in extreme high latitude environmental conditions. Intertidal and subtidal limpet species are frequently identified taxa of these archaeological deposits. We investigated whether shell δ18O of the limpet species Nacella deaurata is a valuable record of local sea surface temperature (SST) and ambient water δ18O (δ18Ow) fluctuations, and in turn can be used to estimate the season of its exploitation by Holocene HGF. Sequential shell δ18O of modern species track seasonal changes of SST and δ18Ow. The comparison of shell δ18O profiles of N. deaurata and Nacella magellanica (a coexisting species) suggests the occurrence of distinct growth rate and physiological adaptations between species. Shell δ18O of zooarchaeological specimens of N. deaurata from Lanashuaia II suggests that animals were exploited predominantly in winter and that experienced similar environmental conditions of present day at ∼1320 years BP. Results also indicate that N. deaurata is a valuable candidate for studying past seasonal changes in SST and δ18Ow in this southernmost part of South America.